SOCIAL MEDIA TO BOOST STUDENT COMMUNICATIVE COMPETENCE - Yuyun Yulia; Febriana Eko Prasetyawati (ETERNAL (English Teaching Journal), 2022)
Online learning or people in Indonesia called as pembelajaran dalam jaringan (daring) has been widely used in teaching and learning particularly in pandemic Covid-19. Teachers try hard to create interesting activities with social media as a means for students to develop their communicative competence. This paper is to describe the implementation of Instagram Live Streaming as the media platform for speaking activity in vocational school as well as to reveal the students' perception after implementing Instagram Live Streaming in their speaking activity. This is a descriptive qualitative research for the 11th grader students of a vocational school in rural area. Findings show teachers implemented Instagram Live Streaming in the 2013 curriculum consisting of observing, questioning, experimenting, associating and communicating. This application is applied on the communicating phase. Students’ responses are positive due to its benefits on improving students speaking skills in particular on pronunciation, intonation, and self- confidence